Much ado about nothing - Shakespeare, William, 1564-1616 (Floating Press, 2008)
Shakespeare''s comedy play Much Ado About Nothing pivots around the impediments to love for young betrothed Hero and Claudio when Hero is falsely accused of infidelity and the ""lover''s trap"" set for the arrogant and assured Benedick who has sworn of marriage and his gentle adversary Beatrice. The merry war between Benedick and Beatrice with the promptings of their friends soon dissolves into farcical love, while Hero''s supposed infidelity is shown to be little more...